The impact of 3D printing on trade and FDI - Ana Lucia Abeliansky; Inmaculada Martinez-Zarzoso; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes the effects of 3D printing technologies on the volume of trade and on the structure of foreign direct investment (FDI). A standard model with firm-specific heterogeneity generates three main predictions. First, 3D printers are introduced in areas with high economic activity that also face high transport costs. Second, technological progress in 3D printing leads to FDI dependent on traditional production structures gradually being replaced with FDI based on 3D printing techniques. At this stage, international trade remains unaffected. Finally, at later stages, with 3D printers being widely used, further technological progress in 3D printing leads to a gradual replacement of international trade. Empirical evidence indicates that countries subject to higher transport costs and with high levels of economic activity are indeed among those importing more 3D printers. Anecdotal evidence also supports the second and third predictions of the model.
Keywords: F10; F23; O33; 330